The Role of Internal Audit in Ensuring Compliance with Risk Management Policies: Systematic Literature Review - Alfina Alfina; Anak Agung Gde Satia Utama (Green Publisher Indonesia, 2025)
This study aims to examine the role of internal audit in risk management, fraud prevention, and the implementation of Good Corporate Governance (GCG) principles in various organizations. This research employs the Systematic Literature Review (SLR) method to analyze relevant studies concerning the role of internal audit in these contexts. The analysis results indicate that internal audit plays a crucial role in ensuring effective risk management, fraud detection and prevention, and strengthening corporate governance. Internal audit functions to identify and manage various types of risks, including financial, operational, and reputational risks, as well as enhancing transparency in risk management disclosures. Furthermore, internal audit has proven effective in preventing fraud through the implementation of stringent internal controls. This study concludes that internal audit significantly contributes to the success and sustainability of organizations, serving as the frontline in maintaining organizational integrity and strengthening the application of GCG principles. Therefore, internal audit plays a strategic role in enhancing overall company performance.